A Systematic Review of Supportive Therapy Effect on Quality of Life in Cancer Patients - Suharyono Suharyono; Suhendra Agung Wibowo; Ira Purnamasari; Tintin Sukartini (Jurnal Ners, 2020)
Introduction: Supportive therapy is considered an important element in the treatment of cancer patients which is often associated with efforts to overcome life-threatening problems. However, the application of this intervention in clinical practice has not yet been fully carried out. This systematic review summarizes the evidence regarding the effect of supportive therapy in improving the quality of life (QoL) of cancer patients.Methods: The review was performed according to PRISMA guidelines. We searched four electronic databases to identify studies comparing patients who received specific protocol interventions with the control group. The keywords used are "Supportive Therapy" AND "Palliative Supportive Care" AND "Quality of Life" OR "Health Quality" OR "Health-Related Quality of Life".Results: In the study, the average quality of life assessment was carried out at 12 weeks and six months after the intervention. Seven7 of the 15 studies used QLQ-C30 to measure the quality of life of patients with cancer, which was managed to validate and assess the quality of life in patients with cancer, whereas of the 15 studies evaluating results reported, patients reported differences in favor of the intervention group.Conclusion: The overall methodology quality is good. Several comparative studies have evaluated the impact of supportive therapy on the quality of life of cancer patients. The quality of this study is good and the results are acceptable in improving the quality of life of cancer patients undergoing chemotherapy treatment, and palliative care.